CODE SWITCHING & CODE MIXING IN RITSUKI’S VLOG ON DIGITAL MEDIA TIKTOKː A STUDY OF SOCIOLINGUISTICS - Wardhani, Dixy Putri; Yanuar Arifin (Esteem Journal of English Education Study Programme, 2025)
In the digital era, multilingualism is increasingly visible on social media platforms like TikTok. This study examines Code Switching and Code Mixing in multilingual communication by analyzing content from the TikTok account Mega Kenichiro Official (Ritsuki’s Vlog) through a sociolinguistic perspective. The objective is to understand how speakers use Indonesian, Japanese, and Javanese in daily interactions and its impact on digital communication. Using a qualitative approach, the study analyzed 20 selected vlogs through note-taking, focusing on intra-sentential and intra-lexical code mixing, as well as inter-sentential code switching. The conversations were classified based on speakers and language patterns. The findings show that Japanese words are frequently mixed into Indonesian sentences, while code switching between Indonesian and Javanese occurs mostly in complete sentences. Additionally, the influence of these linguistic patterns extends to audience interactions, as reflected in their comments. This study concludes that multilingualism plays a significant role in shaping online discourse, making digital media a dynamic space for language interaction. Future research should explore the educational implications of code switching and code mixing in language learning.